2020
DOI: 10.3390/w12123435
|View full text |Cite
|
Sign up to set email alerts
|

Technological Reliability and Efficiency of Wastewater Treatment in Two Hybrid Constructed Wetlands in the Roztocze National Park (Poland)

Abstract: The paper presents the results of a 3-year study on the technological reliability and the efficiency of typical domestic wastewater treatment in two hybrid constructed wetland systems (CWs) located in the area of the Roztocze National Park (Poland). The studied objects consist of an initial settling tank and a system of two beds of the vertical flow (VF) and horizontal flow (HF) (VF–HF) type with reed and willow. The wastewater flow rate in the constructed wetlands systems (CWs) was 0.4 and 1.0 m3/d, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Table 5 shows the mean removal efficiencies (%) that were obtained on the basis of the mean values of the parameters that were measured at each of the sampling points of the study, comparing the water quality of the influent (C influent ) and the effluent (C effluent ) of each of the treatment stages [ 19 ], as follows: % = 100 × (1 − C effluent /C influent ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 5 shows the mean removal efficiencies (%) that were obtained on the basis of the mean values of the parameters that were measured at each of the sampling points of the study, comparing the water quality of the influent (C influent ) and the effluent (C effluent ) of each of the treatment stages [ 19 ], as follows: % = 100 × (1 − C effluent /C influent ) …”
Section: Resultsmentioning
confidence: 99%
“…One such system, which has been used over the last 60 years worldwide, is the constructed wetland (CW) wastewater treatment plant. Of these, hybrid constructed wetland systems (HCWS), particularly the vertical-flow–horizontal-flow type, are specifically recommended as they ensure high efficiency in wastewater treatment with a relatively low energy demand [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many years of studies of various constructed wetlands in Poland and around the world have demonstrated that systems with several soil-plant beds and different wastewater flow regimes show a higher efficiency of pollutants removal, both organic and biogenic, than single-stage systems [26,27,43,45,46,48,50,51].…”
Section: Pollutants Removal Efficiencymentioning
confidence: 99%
“…The efficiency and reliability of constructed wetlands are the focus of research conducted by a growing number of scientists around the world. The operation of small constructed wetlands (<2000 PE) has been analyzed both in Poland [21,26,[42][43][44][45][46] and in other countries worldwide [47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of the effectiveness of neutralization and removal of pollutants in wastewater treatment plants located in areas with no sewer systems are mainly focused on the removal of organic pollutants as well as nitrogen and phosphorus, i.e., factors responsible for water eutrophication and soil contamination [1,3,4,[7][8][9][10][11][12]. Given the fecal load and contamination with intestinal bacteria in domestic wastewater, greater attention has been paid to the characterization and elimination of these microorganisms, including pathogenic bacteria [12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%